Penggunaan Kriptografi Asimetris dalam Pengamanan Komunikasi IoT - Alfatah, Dhika (Jurnal Komputer, 2024)
The Internet of Things (IoT) has grown rapidly and become an important part of many sectors, from industry to healthcare to households. However, this growth also increases security risks, especially regarding data communication between devices. One promising solution is the implementation of asymmetric cryptography, which offers encryption and decryption mechanisms using public and private key pairs. This article discusses how asymmetric cryptography can be applied in IoT systems to maintain data confidentiality, integrity, and authentication. In addition, implementation challenges such as limited computing power and energy consumption in IoT devices are analysed, as well as solutions that can be applied to overcome them. This study shows that despite technical barriers, the use of asymmetric cryptography remains relevant and effective as a layer of protection in an increasingly complex IoT ecosystem.